The Influence of Financial Literacy on Gold Investment Interest (A Study of Students at Ma'arif University, Lampung) - Adien Wahyu Lestari; Eka Nurzanah (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the influence of financial literacy, consisting of financial knowledge, financial skills, and financial confidence, on gold investment interest among students at Ma'arif University, Lampung. The research method used was a quantitative approach with a survey type, involving 103 respondents selected using a purposive sampling technique. Data were collected through a Likert scale questionnaire and analyzed using multiple linear regression with the help of the SPSS application program. The results showed that partially, financial knowledge and financial skills did not have a significant effect on gold investment interest. Conversely, financial confidence proved to have a positive and significant effect and was the most dominant variable. Simultaneously, the three independent variables had a significant effect on gold investment interest. The coefficient of determination (R-Square) value showed that the model was able to explain 40.5% of the variation in investment interest, while the remaining 59.5% was influenced by other factors outside the study. These findings confirm that psychological aspects, especially financial confidence, have a significant role in driving student investment interest compared to aspects of knowledge and skills alone.